Cerebral sex dimorphism and sexual orientation. Issue 3 (11th December 2017) - Manzouri, Amirhossein; Savic, Ivanka
Abstract: The neurobiology of sexual orientation is frequently discussed in terms of cerebral sex dimorphism (defining both functional and structural sex differences). Yet, the information about possible cerebral differences between sex‐matched homo and heterosexual persons is limited, particularly among women. In this multimodal MRI study, we addressed these issues by investigating possible cerebral differences between homo and heterosexual persons, and by asking whether there is any sex difference in this aspect. Measurements of cortical thickness (Cth), subcortical volumes, and functional and structural resting‐state connections among 40 heterosexual males (HeM) and 40 heterosexual females (HeF) were compared with those of 30 homosexual males (HoM) and 30 homosexual females (HoF). Congruent with previous reports, sex differences were detected in heterosexual controls with regard to fractional anisotropy (FA), Cth, and several subcortical volumes. Homosexual groups did not display any sex differences in FA values. Furthermore, their functional connectivity was significantly less pronounced in the mesial prefrontal and precuneus regions. In these two particular regions, HoM also displayed thicker cerebral cortex than other groups, whereas HoF did not differ from HeF. In addition, in HoM the parietal Cth showed "sex‐reversed" values, not observed in HoF. Homosexual orientation seems associated with a less pronounced sexual differentiation of white matter tracts and a less pronounced functional connectivity of the self‐referential networks compared to heterosexual orientation. Analyses of Cth suggest that male and female homosexuality are not simple analogues of each other and that differences from heterosexual controls are more pronounced in HoM.